South China Karst II - Knez, Martin (Carsologica, 2011)
Slovene and Chinese karstologists join studies from the chosen parts of diverse Yunnan karst, from topical cone karst on south and stone forest on center to mountain karst and high plateau karst of Tibet in the north. Presented are results of research in the karst on stone forests and other types of karst surfaces, soil erosion, the formation of tufa, vegetation, the development, age and sediment of karst caves, karst waters, epikarst fauna and the protection of the natural heritage.